Analytical study of the behavior research and trends among the faculty members for using the Saudi Digital Library : A model of the Applied College at Northern Border University - AlSawy, Yaser (Al-Adab Journal, 2023)
The study aimed to analyze the research behavior of using the Saudi Digital Library, the associated trends among faculty members for the Applied College at Northern Border University, where the researcher sought to apply the standards of the survey and analytical approaches, with the preparation of a questionnaire as a main measurement tool for the study, the study sample consisted of 31 faculty members, out of the total faculty members in the college, representing 61%, the study found a high number of faculty members using the Saudi digital library with a relative increase in upgrading scientific research skills, preparing studies and research and academic advancement, with a medium impact on improving the educational process And the high compatibility of the Saudi digital library with the academic curricula. The study also recommended the necessity of holding specialized workshops for faculty members to use the research systems, its components, the search results for databases, and the use of digital resources from all places of access to the library, while linking them to study assignments with students.